Do green accounting and sustainability performance improve energy firms’ financial performance? - Gema Sri Basyir; Lilik Handajani; Ayudia Sokarina (Postgraduate Program Merdeka University, 2026)
This study aims to analyze the effect of green accounting and sustainability performance on the financial performance of energy sector companies listed on the Indonesia Stock Exchange. The research sample consisted of 15 energy sector companies during the 2019–2024 period, with a total of 90 observations obtained through purposive sampling. This study employed a quantitative approach using panel data regression analysis techniques. The results indicate that green accounting has a positive and significant effect on financial performance as measured by ROA and ROE, but a negative and significant effect on market performance as measured by Tobin’s Q. These findings suggest that environmental accounting practices provide more evident benefits for the company’s internal profitability, although such practices have not yet been fully perceived positively by the market. Meanwhile, sustainability performance, proxied by PROPER, has no significant effect on financial performance as measured by ROA and ROE, nor on market performance as measured by Tobin’s Q, indicating that environmental performance has not yet been translated into an increase in the company’s economic value. The implications of this study suggest that energy sector companies need to integrate green accounting and sustainability practices more strategically, so that they are not merely compliance-oriented, but are also able to strengthen internal profitability and enhance firm value in the long term.